2018
DOI: 10.1080/10962247.2017.1415236
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particulate emissions from Australian open-cut coal mines: Toward improved emission estimates

Abstract: Development of region-specific emission estimation techniques for PM and PM from open-cut coal mines is necessary to allow accurate prediction of particulate emissions to inform regulatory decisions and for use in modeling predictions. Comprehensive air quality monitoring was undertaken, and corresponding recommendations were provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In particular, dust concentration from drilling activities spreads up to 80-100 m from the source, where the heavier fractions of dust settle [44]. For this reason, some authors suggest that the proportion of fine dust tends to increase with increasing distance from the source [49], as PM 10 can travel up to 100 km (or more) and stay in the atmosphere for days, whereas PM 2.5 can travel as far as thousands of kilometres, staying in the air for weeks. Coarse particulates usually deposit quickly and within short distances of the source [3].…”
Section: Technical Variables Distancementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, dust concentration from drilling activities spreads up to 80-100 m from the source, where the heavier fractions of dust settle [44]. For this reason, some authors suggest that the proportion of fine dust tends to increase with increasing distance from the source [49], as PM 10 can travel up to 100 km (or more) and stay in the atmosphere for days, whereas PM 2.5 can travel as far as thousands of kilometres, staying in the air for weeks. Coarse particulates usually deposit quickly and within short distances of the source [3].…”
Section: Technical Variables Distancementioning
confidence: 99%
“…Despite the experimental protocol of each paper, only 15 out of the 24 papers referred to dust-particle size [6,22,24,25,28,31,[43][44][45]48,49,51,52,55,56]. The remaining papers did not specify this parameter, despite mentioning "respirable dust" [41,47,53], "respirable and inhalable" [42,54], or just "dust" [32,50].…”
mentioning
confidence: 99%
“…Compared with other countries, the concentration of PM 10 in major Australian cities is relatively low ( Liu et al, 2019a ). The Australian National Pollutant Inventory (NPI) has identified open-cut coal mines as the most significant source of PM emissions, with approximately 25% of industrial emissions arising from coal mining activities ( Richardson et al, 2018 ). Furthermore a recent study, has shown the PM 10 concentrations in Australia are higher in coal mining towns than non-mining urban and rural regions ( Hendryx et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surrounding Moranbah are several large, operational, open-cut coal mines (see Fig. 1 ), which provide a potential source of dust to the local population ( Alvarado et al, 2015 ; Richardson et al, 2018 ; Ghose and Majee, 2007 ; National Pollutant Inventory (NPI), 2020 ) (see Supplementary Fig. 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the Sparse Matrix Operator Kerner Emissions Modeling System (SMOKE), developed by the Center for Environmental Modeling for Policy Development (CEMPD), which is based on RatePerStart (RPS) emission rates [15]. However, the results from the emission models could be wrong even if representative source profiles are used, and thus a contradiction in the empirical evidence for ground-level monitoring could appear [16][17][18][19][20][21][22]. On the other hand, measures of PM 2.5 from monitoring stations on the surface could be used in statistical models under a dispersion modelling approach.…”
Section: Introductionmentioning
confidence: 99%